Physics and Whitehead: An Alternative Approach - Athearn, Daniel (Process studies, 2011)
While efforts to frame a Whiteheadian response to problems of quantum interpretation have looked primarily to the later metaphysical writings, a powerful potential in this regard is contained in the ideas of the philosophy of nature period.